2015
DOI: 10.5901/mjss.2015.v6n6s1p259
|View full text |Cite
|
Sign up to set email alerts
|

“Why Do I Feel So Bad?” Childhood Experiences of Emotional Neglect, Negative Affectivity, and Adult Psychiatric Symptoms

Abstract: The purpose of this study was to examine the relationship between childhood experiences of emotional neglect, negative affectivity, and adult psychiatric symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The psychometric properties of the PBI are good, with good internal consistency, high test-retest reliability, and considerable support for its validity as a measure of actual parenting in both clinical and nonclinical samples (Parker, 1989). The Italian translation of the PBI (Scinto, Marinangeli, Kalyvoka, Daneluzzo, & Rossi, 1999) was used in this study, and consistent with previous research (Schimmenti et al, 2015b) an index on childhood emotional neglect was calculated by subtracting the sum of PBI maternal and paternal care scores from the sum of PBI maternal and paternal overprotection scores, that is: [(PBI mother's overprotection ϩ PBI father's overprotection) Ϫ (PBI mother's care ϩ PBI father's care)]. Therefore, higher scores on this index indicate higher exposure to parental emotional neglect during childhood.…”
Section: Methodsmentioning
confidence: 95%
“…The psychometric properties of the PBI are good, with good internal consistency, high test-retest reliability, and considerable support for its validity as a measure of actual parenting in both clinical and nonclinical samples (Parker, 1989). The Italian translation of the PBI (Scinto, Marinangeli, Kalyvoka, Daneluzzo, & Rossi, 1999) was used in this study, and consistent with previous research (Schimmenti et al, 2015b) an index on childhood emotional neglect was calculated by subtracting the sum of PBI maternal and paternal care scores from the sum of PBI maternal and paternal overprotection scores, that is: [(PBI mother's overprotection ϩ PBI father's overprotection) Ϫ (PBI mother's care ϩ PBI father's care)]. Therefore, higher scores on this index indicate higher exposure to parental emotional neglect during childhood.…”
Section: Methodsmentioning
confidence: 95%
“…There is compelling scientific evidence which introduces childhood neglect as a risk factor for mental disorders in adulthood [ 25 ]. In a study in Italy, a strong relationship was observed between parents’ emotional neglect and children’s mental disorders [ 26 ]. Emotional neglect usually stems from a parent’s failure or refusal to satisfy their children’s psychological needs.…”
Section: Discussionmentioning
confidence: 99%
“…relationship was observed between parents' emotional neglect and children's mental disorders [25]. Emotional neglect usually stems from a parent's failure or refusal to satisfy their children's psychological needs.…”
Section: Discussionmentioning
confidence: 99%